2015
DOI: 10.1016/j.jped.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of different measures of adiposity to distinguish between low/high motor coordination

Abstract: Body fat percentage and waist circumference showed a slightly better discriminatory accuracy in predicting low motor coordination for females and for males, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 29 publications
1
20
1
9
Order By: Relevance
“…In contrast to the study by Lopes et al (), which suggests alterations in the association between adiposity indicators and motor coordination according to sex in young children from 9 to 12 years old, the present study shows that the associations found are independent of the child's sex. According to Malina, Bouchard, and Bar‐Or () are not expected morphology differences between boys and girls in preschool age, as well as gains in stature are similar throughout early childhood (Santos et al, ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the study by Lopes et al (), which suggests alterations in the association between adiposity indicators and motor coordination according to sex in young children from 9 to 12 years old, the present study shows that the associations found are independent of the child's sex. According to Malina, Bouchard, and Bar‐Or () are not expected morphology differences between boys and girls in preschool age, as well as gains in stature are similar throughout early childhood (Santos et al, ).…”
Section: Discussioncontrasting
confidence: 99%
“…Studies evaluating the relationship between MC and central obesity, particularly WHtR, are scarce. Lopes, Santos, Moreira, Pereira, and Lopes () evaluated whether different measures of adiposity (BMI, waist circumference, WHtR, and% body fat) were related to low motor coordination in children aged 9 to 12 years. Their results showed that in girls the % body fat and waist circumference were associated with low motor coordination, but among boys all adiposity indicators, including WHtR, were associated with low motor coordination.…”
Section: Introductionmentioning
confidence: 99%
“…In recent study with children of both sexes, Lopes et al8 reported that, in addition to BMI, waist circumference, height-waist ratio, and body fat percentage also were associated with performance on KTK. However, fat percentage ( β =2.395, 95%CI 1.234-4.646; p =0.010) showed higher sensitivity to predict low motor coordination in girls.…”
Section: Discussionmentioning
confidence: 99%
“…, 8 However, there is a lack of studies in the literature describing the multiple factors that may be related to motor development of children, including the biological maturation. The studies performed with the KTK test battery aimed primarily at the association of the anthropometric characteristics of children and youth, especially body mass index (BMI), with test performance 7…”
Section: Introductionmentioning
confidence: 99%
“…Considering the % BF, we can see an inverse relationship between excess body fat and motor performance. In a Portuguese study that analysed 596 children aged 9 to 12 years, lower motor coordination was observed in boys and girls with a high percentage of fat 29 . Excess body fat, from a mechanical perspective, represents an inert load that must be moved and, generally, negatively influences motor performance 20 .…”
Section: Discussionmentioning
confidence: 99%